Chinese firms entering China's low-income market: Gaining competitive advantage by partnering governments - Genia Kostka; Jianghua Zhou (Frankfurt School of Finance & Management, 2010)
This paper investigates poverty alleviation efforts in China and the nature of governmententerprise partnerships there. We argue that firms partnering central and local governments can be an effective strategy to overcome resource-based obstacles in low-income markets. In China, local and central governments are owners of rare and valuable resources, thus offering better access to finance, infrastructure, technical and planning expertise, advocacy through government marketing and distribution channels, and links to other stakeholders. The findings are based on 16 case studies of firms entering the low-income market in China, of which two cases in the agricultural and telecommunication sector are studied in depth.
Keywords: M19; O18; R51; R59; 330; Partnerships; government; poverty alleviation; China; base of the pyramid; Armutspolitik; Public-Private Partnership; Markteintritt; Strukturschwacher Raum; China